Digital resources integration under the knowledge management model: an analysis based on the structural equation model. Issue 4 (5th June 2020) - Rafi, Muhammad; JianMing, Zheng; Ahmad, Khurshid
Abstract : Purpose: In the age of knowledge explosion, modern technology facilitates the acquisition, organization and effective dissemination of information to support academic research. To achieve long-term educational goals, integrating digital resources into a knowledge management model (KMM) has become a necessary prerequisite for university management. The proposed KMM aims to combine resources and technology to facilitate resource management, navigation and cross-database search for advanced research. Design/methodology/approach: The published literature on digital resource integration was reviewed, and the status of resource organization was discussed with experts to compile research instruments together with the perspectives of serving professionals in universities. The data obtained was systematically processed to develop an integrated resource KMM. Data volume measurement was done with the SPSS software and AMOS was used for path analysis and modeling. After the conceptual model was developed, many assumptions were associated with it, and the software was run on the data set to validate the proposed theoretical model. Findings: Library resources with four components (digital resources, information technology, financial planning and service promotion) have been successfully integrated into the knowledge management framework to organize resources and provide academic services for researchers. In addition to the organization of digital resources, the two components of knowledge management, such as the explicit knowledge of its technology-oriented nature and the tacit knowledge of its human-centered positions, remained useful to strengthen the integration process. Practical implications: With the development of digital technology and the internet, information authentication, access and dissemination have become a complex task for information centers. As an integral part of modern digital libraries, the expansion of digital collections requires proper accessibility organization. Owing to the increasing number of digital resources, organization and management require thorough research and appropriate integration mechanisms. This integrated KMM helps to organize heterogeneous information resources and databases in libraries for long-term academic tasks. Originality/value: Based on literature studies and discussions with academic experts, integration problems were identified, and raw data were obtained from the library management to find a solution. It is unique research owing to a lack of original work and extensive international literature on resource integration in connection with KMMs. This study has innovative findings that can add value to world literature.